Perception of the health of second-generation atomic bomb survivors - Oishi, Kodai; Urata, Hideko; Hayashida, Naomi; Shinkawa, Tetsuko; Nagata, Akira; Kondo, Hisayoshi; Sato, Nana; Shibata, Hisami; Matsuo, Honami; Yoshimatsu, Naoki; Takahira, Hitomi; Takamura, Noboru (The Journal of Radiological Nursing Society of Japan, 2022)
Preceding studies report that second-generation atomic bomb survivors (SGSs) have health anxiety about the hereditary effects of radiation when they get a physical illness, and subconsciously continue to worry about the cause. Based on this, it was expected that the fact that they are SGSs themselves affects their thoughts on their own health. We conducted comparisons between “SGSs and Non-SGSs” and “SGSs with health anxiety caused by being SGSs and SGSs without this health anxiety” to clarifying the characteristics of their way of thinking regarding their health. Results from these analyses show there was no difference in their thought on their own health between SGSs and Non-SGSs however, this factor was considered to be a factor specific to Nagasaki and Hiroshima. On the other hand, SGSs with this health anxiety is independently associated with “Self-rated health is not healthy” and “Being SGSs is the cause of threatened health”. It was revealed from the descriptive contents of this health anxiety that “Parent’s cancer” and “Parent’s death by cancer” were factors of this health anxiety.